Employee job satisfaction – reviewing on the basis of Dhaka Bank Limited, Mohakhali Branch - Mahmud, Sumya (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.